Occult cancer detection in patients with hemostatic disorder and venous thromboembolism. Issue 163 (March 2018) - Husseinzadeh, Holleh; Carrier, Marc
Abstract: There are physiologic ties between Von Willebrand Factor (VWF) and circulating tumor cells. VWF appears to play a role in tumor biology, but it is unclear whether cancer behavior differs in Von Willebrand Disease. In patients presenting with venous thromboembolism (VTE), occult cancer is frequently considered as an underlying cause. The prevalence of occult cancer after provoked VTE is low (3%); therefore, cancer screening in these patients is not routinely recommended. In those with unprovoked VTE, occult cancer is more prevalent, estimated between 4 and 10%. Due to this elevated risk, occult cancer screening is recommended in this population. Multiple studies have investigated whether a "limited" approach (including history and physical exam, basic labs, and chest X-ray) versus "extensive" approach (addition of advanced imaging, such as computer tomography) is more effective. Current data fails to demonstrate extensive screening strategies diagnose more occult cancer, miss fewer cancers during follow up, or improve cancer-related mortality. Furthermore, many patients may be needlessly exposed to unnecessary diagnostic procedures with their associated complications and costs, as well as significant anxiety. Therefore, the decision to perform additional testing should be made on a case-by-case basis. Additional studies are needed to identify subgroups of patients with unprovoked VTE at highest risk for occult cancer. Highlights: vWF may play a role in tumor biology. Cancer behavior in vWD is unknown. Provoked VTE does not warrant routine cancer screening Occult cancer is detected in 5% of patients with unprovoked VTE Limited screening detects 90% of occult cancers after unprovoked VTE Evidence does not support extensive cancer screening in unprovoked VTE.